Analyzing the profile of the manager from the perspective of the employees: A case study - Albuquerque, André; Melo, Fagner José Coutinho de; Xavier, Larissa; Medeiros, Denise Dumke (Brazilian Journal of Operations & Production Management, 2021)
Goal: This paper proposes to study the leader’s profile using the Johari Window to establish feedback on the leader’s behavior in comparison with the employees’ point of view. Design / Methodology / Approach: The case study was carried out in a given material distribution center for civil construction through a questionnaire, based on the Johari window model. The research was classified as applied, exploratory, qualitative and case study. Results: Most of the respondents in the surveyed sector have the opinion that their leader is inserted in the “blind” area of Johari window, that is, it is an area unknown to the leader, either because subordinates do not want to share feedback or because the leader is not able or does not care about it. Through these results, improvements were proposed. Limitations of the investigation: The questionnaire was only applied in one moment, and it is not possible to compare the leader’s Johari window with the posterior view of each team member. Practical implications: When leaders share their way of thinking and acting and are willing to receive feedback, there will be greater clarity in communication and executing objectives. With this, it is possible to obtain more qualified and motivated personnel for the performance of the organization’s activities, reducing costs, increasing productivity, generating a competitive advantage. Originality / Value: Understanding the relationship between the leader and followers in the researched sector, verifying the confrontation of the opinion of the followers about the behavior of the leader in order to improve the organizational environment to achieve the objectives.